L’écriture polymorphe de la masculinité chez Rabelais - David LaGuardia (Itinéraires)
The polymorphous writing of masculinity in Rabelais’s works assumes at least two forms: first, apostrophes enunciated by a masculine subject who calls out to other men through affectionate insults written in a comic register, in order to allay the anxieties that the speaking subject has concerning his gender; and secondly, verbal improvisations based on the idea or image of the male body’s private parts as they are made manifest in external signs, such as the beard and the codpiece, meant to be read and recognized by others of both sexes. Rabelais’s writing of masculinity is hence discursive and intersubjective, and situates the “being” of masculine subjects within the incessant mode of semantic displacement that is characteristic of his works.